ANALISIS FAKTOR-FAKTOR KONSUMEN DALAM MEMILIH BELANJA DI ONLINE STORE DARIPADA OFFLINE STORE - Frahyanti, Fitroh; Syafi’i, M. Aris; Sista Devi, Happy (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This research use desciptive qualitative approach. Interviews function as a guide for researchers to use the current social situation that will be researched thoroughly, broadly and in depth. All words written or spoken by an individual and observed behavior are included in this data. This research examines the lifestyle symptoms of JKT48 fans, describing the feelings and perspectives of the participants. People around the world began to be tainted by various Japanese cultural products, including films, songs, fashion, lifestyle, and industrial products. Japanese culture spread so quickly and was widely embraced by society, giving rise to the phenomenon of Japaneseophilia, also known as Wibu, or in JKT48 life, usually called Wota. Wibu is a term that refers to the popularity of Japanese culture abroad, especially overseas, to refer to the spread of South Japanese pop culture throughout the world, including in Indonesia. Indonesian teenagers have become interested in Japanese culture or J-pop recently. JKT48 fans, such as FJKT48, the capital's idols, and the JKT48 gallery, know that J-pop is not just about music. It is closer to all Japanese culture. even fans apply elements of Japanese culture in their daily lives. Japanese fashion is something that is very common in various parts of the world, and the world of fashion is growing rapidly, especially Japanese fashion which has influenced hairstyles, dresses, shoes, even make-up. Japanese fashion is unique because it represents bright clothing colors that are easy to combine with the body and skin colors of Asian people. Japanese fashion is also present and influences its followers in everyday life. They believed that following these developments was in keeping with the emerging modernity. From here we can find out how the problem of lifestyle dependency has an impact on the behavior of Indonesian people.